Renal glomerular and tubular responses to glutaraldehyde- polymerized human hemoglobin - Williams, Matthew C.; Zhang, Xiaoyuan; Baek, Jin Hyen; D’Agnillo, Felice (Frontiers in Medicine, 2023)
Hemoglobin-based oxygen carriers (HBOCs) are being developed as oxygen and volume replacement therapeutics, however, their molecular and cellular effects on the vasculature and different organ systems are not fully defined. Using a guinea pig transfusion model, we examined the renal glomerular and tubular responses to PolyHeme, a highly characterized glutaraldehyde-polymerized human hemoglobin with low tetrameric hemoglobin content. PolyHeme-infused animals showed no major changes in glomerular histology or loss of specific markers of glomerular podocytes (Wilms Tumor 1 protein, podocin, and podocalyxin) or endothelial cells (ETS-related gene and claudin-5) after 4, 24, and 72 hours. Relative to sham controls, PolyHeme-infused animals also showed similar expression and subcellular distribution of N-cadherin and E-cadherin, two key epithelial junctional proteins of proximal and distal tubules, respectively. In terms of heme catabolism and iron-handling responses, PolyHeme induced a moderate but transient expression of heme oxygenase-1 in proximal tubular epithelium and tubulointerstitial macrophages that was accompanied by increased iron deposition in tubular epithelium. Contrary to previous findings with other modified or acellular hemoglobins, the present data show that PolyHeme does not disrupt the junctional integrity of the renal glomerulus and tubular epithelium, and triggers moderate activation of heme catabolic and iron sequestration systems likely as part of a renal adaptive response.